2016
DOI: 10.1016/j.addbeh.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

The within-person association between alcohol use and sleep duration and quality in situ: An experience sampling study

Abstract: Objective Despite evidence for detrimental effects of alcohol on sleep quality in laboratory studies, alcohol is commonly used as a self-prescribed sleep aid. This study examined the within-person associations of alcohol use with sleep duration and quality in everyday life to gain insight into the ecological validity of laboratory findings on the association between sleep and alcohol. Method A sample of 150 adults (age 19–89 years) were followed for 60+ days as part of an intensive experience sampling study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…Notably, a significantly positive association between PSQI total score and alcohol consumption was also observed in our study. Previous studies also reported significant associations between alcohol consumption and sleep quality [ 8 , 9 , 10 , 11 ]. This is due to the fact that alcohol could reduce genioglossal muscle tone, lead to upper airway collapse [ 41 ] and increase the upper airway resistance [ 42 ], and finally contributed to the risk of obstructive sleep apnoea (OSA) [ 8 ].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Notably, a significantly positive association between PSQI total score and alcohol consumption was also observed in our study. Previous studies also reported significant associations between alcohol consumption and sleep quality [ 8 , 9 , 10 , 11 ]. This is due to the fact that alcohol could reduce genioglossal muscle tone, lead to upper airway collapse [ 41 ] and increase the upper airway resistance [ 42 ], and finally contributed to the risk of obstructive sleep apnoea (OSA) [ 8 ].…”
Section: Discussionmentioning
confidence: 76%
“…It is well known that poor sleep quality contributes significantly to cancer [ 3 ], depression [ 4 ], and dementia [ 5 ]. Unhealthy habits, such as smoking [ 6 , 7 ] and drinking [ 8 , 9 , 10 , 11 ] are associated with poor sleep quality. Besides, the sleep quality of adults has decreased along with lifestyle changes [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the current study examined the association between sleep and craving, and not treatment outcome. Participants exhibited dependence for a range of substances and some were on medications (Table 1), including substances that exert influences on affect and sleep (Lydon et al, 2016; Oberndorfer et al, 2000; Weddington et al, 1990). While this polydrug and medication use does not allow conclusions to be drawn on associations between sleep, craving, affect, and NMUPD specifically, it is representative of NMUPD in the context of other drugs observed in nationally representative samples (McCabe et al, 2008; McCabe et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recent innovations in intensive repeated measures data collection, whereby individuals are repeatedly assessed over timescales much longer than typical scans (e.g., 5 hours of resting state data collection), are providing opportunities to reliably characterize individuals without relying on group level data (Filevich et al, 2017;Gordon et al, 2017;Laumann et al, 2015) Notably, while the intensive repeated measures associated with fMRI data lend themselves to person-specific models, time series approaches capable of capturing heterogeneity across persons may also be applied to behavioral data. This is routinely done (e.g., Lydon et al, 2016;Russell et al, 2016) within the context of multilevel models that accommodate the nested nature (with measurement occasions nested within participants) of repeated measures data (Snijders & Bosker, 2012). In this approach, random effects may be specified for an independent variable.…”
Section: Matching Models and Methodmentioning
confidence: 99%